1993
DOI: 10.1080/10615809308248375
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial correlates of emotional distress and risk behavior in african-american women at risk for hiv infection

Abstract: We examined a model of stress and coping in 749 African-American women at risk for HIV infection. Women in the sample were either homeless, intravenous drug users (IVDUs) sexual partners of IVDUs, or prostitutes. A model was hypothesized based on stress and coping theory and research. Antecedents studied were personal resources, specifically self-esteem and available support. Mediators were threat appraisal and coping efforts. Outcomes studied were emotional distress and HIV risk behaviors. Structural equation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 51 publications
2
25
0
Order By: Relevance
“…Researchers have demonstrated that persons who perceive fewer threats in their environment and who cope more adaptively experience lower levels of emotional distress (Fawzy et al, 1990;Namir, Wolcott, Fawzy, & Alumbaugh, 1987) and engage in less risky behaviors (Nyamathi, Wayment, et al, 1993). The impact of threat appraisal on barriers to condom use is likewise of interest in this study.…”
Section: Theoretical Perspectivementioning
confidence: 99%
See 4 more Smart Citations
“…Researchers have demonstrated that persons who perceive fewer threats in their environment and who cope more adaptively experience lower levels of emotional distress (Fawzy et al, 1990;Namir, Wolcott, Fawzy, & Alumbaugh, 1987) and engage in less risky behaviors (Nyamathi, Wayment, et al, 1993). The impact of threat appraisal on barriers to condom use is likewise of interest in this study.…”
Section: Theoretical Perspectivementioning
confidence: 99%
“…Measures used to construct the latent variables are described below. Content validity of the scales and measures used in the interviews was previously established through review and consensus of a 12-member panel experienced in the areas of AIDS, ethnic/racial diversity, and coping (for more details see Nyamathi, Wayment, et al, 1993). Before the measurement model (CFA) and path models were tested with structural modeling, preliminary exploratory factor analyses were conducted to determine the optimum configuration for each latent construct.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations